2017
DOI: 10.1038/s41598-017-00565-2
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition in neuropsychiatric populations: a comparison of theory of mind in schizophrenia and mesial temporal lobe epilepsy

Abstract: Social cognition deficits are observed both in patients with schizophrenia (SCZ) and in patients with mesial temporal lobe epilepsy (MTLE). This may be due to dysfunction of the amygdala network, which is a common feature of both diseases. In this study, SCZ (n = 48) or MTLE (n = 31) and healthy controls (HC, n = 47) completed assessments of mentalising (Reading Mind in the Eyes Test, RMET) and basic cognitive processing, e.g., working memory, executive functions and psychomotor speed (Trail-Making Test B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
5
14
1
1
Order By: Relevance
“…A falsifying issue is the type of impairments that may occur in mesial temporal lobe epilepsy, i.e., epilepsy at the core structure for forming the episodic and semantic memories that we consider the key to understanding autism. According to novel findings (Okruszek et al, 2017), mesial temporal lobe epilepsy gives rise to social cognitive deficits, including significant mentalizing deficits; these findings support our proposal.…”
Section: Epilepsysupporting
confidence: 86%
“…A falsifying issue is the type of impairments that may occur in mesial temporal lobe epilepsy, i.e., epilepsy at the core structure for forming the episodic and semantic memories that we consider the key to understanding autism. According to novel findings (Okruszek et al, 2017), mesial temporal lobe epilepsy gives rise to social cognitive deficits, including significant mentalizing deficits; these findings support our proposal.…”
Section: Epilepsysupporting
confidence: 86%
“…Regarding the face‐specific processing dysfunction in patients with TLE, using fMRI, Riley et al reported that brain networks involved in facial processing, including the amygdala, show impaired function on the side of seizure onset, accompanied by altered responses on the side contralateral to the seizure . Additionally, a recent metanalysis of patients with mesial TLE concluded that this group has deficits in recognition of facial expressions, which may be due to dysfunction of the amygdala and related structures of the anterior and medial temporal lobes . In a recent fMRI study using a cognitive task associated with theory of mind, Hennion et al reported that patients with right mesial TLE have less intense neural activation in the right fusiform gyrus than do NC.…”
Section: Discussionmentioning
confidence: 99%
“…46 Additionally, a recent metanalysis of patients with mesial TLE concluded that this group has deficits in recognition of facial expressions, 47 which may be due to dysfunction of the amygdala and related structures of the anterior and medial temporal lobes. 48 In a recent fMRI study using a cognitive task associated with theory of mind, Hennion et al 49 reported that patients with right mesial TLE have less intense neural activation in the right fusiform gyrus than do NC. The fusiform gyrus classically plays an important part in facial processing, 50,51 as do the amygdala and other cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…FEDT: Brown et al, 2014;Roberts et al, 2014;Tas et al, 2012;Lindenmayer et al, 2013;Horton & Silverstein, 2008;Fuentes et al, 2011. FEIT, Brown et al, 2014Roberts et al, 2014;Savla et al, 2012;Brekke et al, 2007;Lindenmayer et al, 2013;Rocha & Queirós, 2013;Wang et al, 2013;Sergi et al, 2009;Fuentes et al, 2011;Okruszek et al, 2017;GilSanz et al, 2017;Mervis et al, 2017;Palumbo et al, 2017, MSCEIT: Linke et al, 2015Lin et al, 2013;Minor et al, 2015;Savla et al, 2012;Tso et al 2010;Frajo-Apor, 2016;Lindenmayer et al, 2013;Fanning et al, 2012;Hasson-Ohayon et al, 2015;Rocha &Queirós, 2013;Minor&Lysaker, 2014;Nitzburg et al, 2015;Horan et al, 2012;Rassovsky et al, 2015. The facial affect recognition: Gard et al, 2009; BLERT: Buck et al, 2014;Minor et al, 2015;Buck et al, 2015;Renard et al, 2012;Fanning et al, 2012;Kalin et al, 2015;Thaler et al, 2014;Browne et al, 2016; FEEST: Guastella et al, 2015;…”
Section: Resultsunclassified
“…Instrumentos citados en: RMET:Brown et al, 2014; Fernandez-Gonzalo et al, 2015Guastella et al, 2015;Savla et al, 2012;Buck et al, 2015;Tso et al 2010;Tas et al, 2012;Martínez-Domínguez et al, 2015;Balogh et al, 2014;Woolley et al, 2014;Schimansky et al, 2010;Thaler et al, 2014;Wang et al, 2013; Lysaker et al, 2013b;Lugnegård et al, 2013;Donohoe et al, 2012;Browne et al, 2016;Robertson et al, 2013;Whitton& Henry, 2013; Tas et al, 2013;Köther, U. et Al, 2017.;Gagen, E. et Al, 2017.;Okruszek et al, 2017;EŞSİZOĞLU et al, 2017;Charernboon & Patumanond, 2017. TASIT:Davis et al, 2013;Wynn et al, 2010;Woolley et al, 2014;Sparks et al, 2010;Kalin et al, 2015;Horan et al, 2012;Browne et al, 2016;Rassovsky et al, 2015;McDonald, 2017; Mervis et al, 2017;Palumbo et al, 2017.…”
mentioning
confidence: 99%